Increased alpha-defensin expression is associated with risk of coronary heart disease: A feasible predictive inflammatory biomarker of coronary heart disease in hyperlipidemia patients - Yaowapa Maneerat (2018)
© 2016 The Author(s). Background: Atherosclerosis is a multifactorial disorder of the heart vessels that develops over decades, coupling inflammatory mechanisms and elevated total cholesterol levels under the influence of genetic and environmental factors. Without effective intervention, atherosclerosis consequently causes coronary heart disease (CHD), which leads to increased risk of sudden death. Polymorphonuclear neutrophils play a pivotal role in inflammation and atherogenesis. Human neutrophil peptides (HNPs) or alpha (α)-defensins are cysteine-rich cation polypeptides that are produced and released from activated polymorphonuclear neutrophil granules during septic inflammation and acute coronary vascular disorders. HNPs cause endothelial cell dysfunction during early atherogenesis. In this cross-sectional study, control, hyperlipidemia and CHD groups were representative as atherosclerosis development and CHD complications. We aimed to assess the correlation between α-defensin expression and the development of CHD, and whether it was a useful predictive indicator for CHD risk. Methods: First, DNA microarray analysis was performed on peripheral blood mononuclear cells (PBMCs) from Thai control, hyperlipidemia and CHD male patients (n = 7). Gene expression profiling revealed eight up-regulated genes common between hyperlipidemia and CHD patients, but not controls. We sought to verify and compare α-defensin expression among the groups using: 1) real-time quantitative RT-PCR (qRT-PCR) to determine α-defensin mRNA expression (n = 10), and 2) enzyme-linked immunosorbent assay to determine plasma HNP 1-3 levels (n = 17). Statistically significant differences and correlations between groups were determined by the Mann-Whitney U test or the Kruskal-Wallis test, and the Rho-Spearman correlation, respectively. Results: We found that α-defensin mRNA expression increased (mean 2-fold change) in the hyperlipidemia (p = 0.043) and CHD patients (p = 0.05) compared with the controls. CHD development moderately correlated with α-defensin mRNA expression (r = 0.429, p = 0.023) and with plasma HNP 1-3 levels (r = 0.486, p = 0.000). Conclusions: Increased α-defensin expression is a potential inflammatory marker that may predict the risk of CHD development in Thai hyperlipidemia patients.